Is Fluid Restriction Really Useful in Chronic Heart Failure? (Revista de Medicina Clinica, 2023)
Editorial on "Is Fluid Restriction Really Useful in Chronic Heart Failure?" presented in volume 7 issue 1 of 2023 of Revista de Medicina  Clínica.
Keywords: Editorial; Fluid Restriction; Chronic Heart Failure